Pretreatment study of food waste using sonication for enhancement of methane production - Md Sabiani, Nor Habsah (2019)
The application of low-frequency ultrasonic pretreatment to the organic fraction municipal solid waste (OFMSW), particularly food waste (FW), is able to overcome slow hydrolysis rate by disintegrating the substrate into a biodegradable substrate. In addition, the process promotes solubilization of organic matter resulting in high amount of substrate readily available within the digestion process and thus enhancing high methane production. The main objective of this study was to obtain high methane production through anaerobic digestion of sonicated food waste. To accomplish this aim, the following objectives were pursued namely correlation between ultrasonication with the physicochemical property changes and anaerobic biodegradability, evaluation of the digester performance and system stability of the anaerobic digestion of the sonicated food waste at different organic loading rate (OLR) and the determination of the kinetic parameters for the performance of the anaerobic digestion of sonicated food waste. The anaerobic digestion experiment on sonicated food waste was conducted in two phases, where in Phase 1, the ultrasonic pretreatment was performed by sonicating 200 mL of food waste slurry at different sonication duration of 2, 4, 6, 8 and 10 minutes at 20 kHz frequency and specific energy input ranged from 5,396 to 25,997 kJ/kg TS, and then anaerobic batch tests were carried out on the sonicated food waste samples. While in Phase 2, the anaerobic digestion was conducted on the sonicated food waste (SFW) and non-sonicated food waste (NSFW) or control in a 13 L laboratory scale anaerobic digester (working volume of 10 L) with increasing organic loading rate (OLR) ranging from 1.5-3.5 gCOD/L.day. The experimental works were carried out in two stages (batch start-up and then continued with semi-continuous feeding). The performance of all digesters was evaluated based on the methane composition, methane production rate as well as methane yield. In the ultrasonic pretreatment (Phase 1), when the specific energy inputs increased from 0 to 25,997 kJ/kg TS, analysis of chemical properties found that the percentage of soluble COD (SCOD) values have increased to 34-40 %. The range of CODsolubilization and degree of disintegration (DD) values were between 11.4-13.4% and 57.15-71.08%, respectively. A linear relationship with an R² of 0.907 was obtained for the correlation between CODsolubilisation and DD. The application of sonicated food waste in the anaerobic digestion process has increased the cumulative CH4 production about 40.3-70.5%. The volume of methane produced was increased from 4.2 liters (non-sonicated food waste) to 7.9 - 14.5 liters in the sonicated food waste. While for Phase 2, the methane composition generated during the process was higher in SFW digester at OLR of 1.5 g COD/L.day and 3.5 g COD/L.day compared to NSFW digester. There was an increase of 9.54-41.28% in methane composition when SFW digester was operated at OLR of 3.5 g COD/L.day. Methane production rate was enhanced by 20.8 -75.7% or 1.26-4.12 times in SFW digester when operated at an OLR of 3.5 g COD/L.day. Methane yields did not show significant changes at the OLR of 1.5 and 2.5 g COD/L.day in both digesters, but started to show a significant increase when SFW digester was operated at OLR of 3.5 g COD/L.day. The methane yield was enhanced by 42.87-82.83% or 1.75-5.82 times at the stated OLR.